Pharmacological approaches to the prevention of myocardial ischemia-reperfusion injury in experimental study and clinical practice - Kozhukhov, S. M.; Parkhomenko, O. M. (Zaporozhye Medical Journal, 2019)
Early reperfusion of the infarct related coronary artery is essential for the preservation of myocardial tissue and improve clinical outcome. The establishment of pharmacological and mechanical reperfusion treatment was a major improvement in the management of patients with myocardial infarction. However, this therapy is often complicated by reperfusion injury including ventricular arrhythmias, myocardial stunning and micro-vascular dysfunction, in addition to significant cardiomyocyte death. The most important factors which contribute to the reperfusion injury are an overproduction of reactive oxygen species, intracellular calcium overload and inflammatory cell infiltration. Some of these mechanisms may be interrelated. From considerations of their nature, an attractive hypothesis has been that some or several of these harmful effects may be counteracted by pharmacological interventions. This hypothesis has mainly been studied in the experimental setting. Objective – in this review, various pharmacological interventions to treat myocardial reperfusion injury including the antioxidant flavonols, glucose – insulin – potassium therapy, adenosine, melatonin, phosphocreatine and cyclosporin A etc. Conclusions. The processes involved in reperfusion injury might provide targets for improved outcomes after myocardial infarction but that aim has thus far not been met in the clinic. By studying new molecules in different experimental settings and protocols, insight has been gained about important factors for possible future clinical applications of drugs with cardioprotective properties.